Photocatalytic Degradation of Alizarin Red-S by Fe-Co Nanoparticles Prepared By Chemical Co-precipitation Method (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
In the present study photocatalytic degradation of hazardous water soluble alizarin red dye by using Fe-Co nanoparticles Â has been investigated. Fe-Co nanoparticles was synthesized by chemical co-precipitation method and characterized by TEM, SEM, EDAX and XRD. The photocatalytic degradation have been studied with the help of variety of parameters such as catalytic dose, dye concentration, pH, contact time and most important chemical oxygen demand. It was observed that The photocatalytic degradation of alizarin red dye by using Fe-Co nanoparticles was an effective ,economic, ecofriendly and faster mode of removing dye from an aqueous solution. The optimum condition for the degradation of the dye was 50 mg/L,pH 8.0, catalyst dose 60 mg/L and contact time 60 minutes. The kinetic studies also have been studied.